2021
DOI: 10.3390/biomedicines9020180
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 10 kHz Spinal Cord Stimulation for the Treatment of Chronic Pain: A Systematic Review and Narrative Synthesis of Real-World Retrospective Studies

Abstract: 10 kHz spinal cord stimulation (SCS) is increasingly utilized globally to treat chronic pain syndromes. Real-world evidence complementing randomized controlled trials supporting its use, has accumulated over the last decade. This systematic review aims to summarize the retrospective literature with reference to the efficacy and safety of 10 kHz SCS. We performed a systematic literature search of PubMed between 1 January 2009 and 21 August 2020 for English-language retrospective studies of ≥3 human subjects imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In the past several years, high-frequency SCS delivered at 10 kHz has been shown to provide superior pain relief to conventional SCS in subjects with chronic low back and leg pain [10][11][12][13] as well as effectiveness in treating chronic peripheral polyneuropathy (PPN) [14,15]; high-frequency SCS offers the advantage of paresthesia-independent pain relief. This prospective study was undertaken in order to evaluate the efficacy and safety of 10-kHz SCS for treating subjects with CPSP.…”
Section: Inclusion Criteria Exclusion Criteriamentioning
confidence: 99%
“…In the past several years, high-frequency SCS delivered at 10 kHz has been shown to provide superior pain relief to conventional SCS in subjects with chronic low back and leg pain [10][11][12][13] as well as effectiveness in treating chronic peripheral polyneuropathy (PPN) [14,15]; high-frequency SCS offers the advantage of paresthesia-independent pain relief. This prospective study was undertaken in order to evaluate the efficacy and safety of 10-kHz SCS for treating subjects with CPSP.…”
Section: Inclusion Criteria Exclusion Criteriamentioning
confidence: 99%
“…Data suggested that the HF-SCS group had a greater response rate relative to LF-SCS and greater pain reduction in both back and leg regions at 24-month follow-up (8). The SENZA series of trials introduced robust data regarding the use of high-frequency 10 kHz SCS and provides substantial evidence that √ is not only safe, but also statistically and clinically effective with demonstrated superiority of high-frequency 10 kHz SCS in contrast to LF-SCS in the treatment of chronic back and neuropathic pain, with level I evidence supported by real-world data studies and clinical experience [67,68,70,84,[109][110][111].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, SCS technology has developed rapidly, resulting in the emergence and adoption of several new stimulation paradigms, including high-frequency 10 kHz SCS (10 kHz SCS), burst stimulation, dorsal root ganglion (DRG) stimulation, and closed-loop SCS [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Never has more choice been available in the field of SCS since the inception of the technology.…”
Section: Introductionmentioning
confidence: 99%